THE ROLE OF BLOCKCHAIN IN REVOLUTIONIZING TRANSPARENCY AND EFFICIENCY IN MODERN BANKING - Yadav, Sameer; Kushwaha, Shubham; Singh, Saurabh; Singh, Tirthraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the transformative role of blockchain technology in modern banking, focusing on its potential to enhance transparency and efficiency. Blockchain, characterized by its decentralized and immutable ledger system, offers significant improvements over traditional banking methods by reducing reliance on intermediaries, mitigating fraud risks, and streamlining transaction processes. The paper reviews existing literature to outline the key advantages of blockchain, including real-time transaction processing through smart contracts and enhanced corporate governance through transparent record-keeping. It also addresses challenges such as scalability and regulatory compliance that banks must navigate in the implementation of blockchain solutions. Ultimately, the findings suggest that while blockchain presents substantial opportunities for revolutionizing the banking sector, careful consideration of its complexities is essential for successful integration.